Predicting Sustainable Consumption of Package-Free Bath Products among Students in Higher Education Institutions - Valentin, Alvin Patrick M (Archīum Ateneo, 2021)
This study examined the applicability of an extended version of the theory of planned behavior in predicting pro-environmental behavior; specifically the purchase behavior of package-free bath products; among students in higher education institutions (HEIs).Design/methodology/approach - Using a non-experimental survey research design; this study empirically tested an extended theory of planned behavior model through structural equation modeling. The data was obtained through a survey of undergraduate students in three HEIs in the Philippines.Findings - Environmental knowledge predicted attitudes toward purchasing package-free bath products. Attitudes; subjective norms; and pro-environmental self-identity predicted intention to purchase package-free bath products. Furthermore; the intention to purchase package-free bath products and perceived behavioral control predicted purchase behavior of the said item.Originality - The findings support the inclusion of environmental knowledge and pro-environmental self-identity to the theory of planned behavior for an integrative model that aims to improve the prediction of the purchase of package-free bath products.Research implications - The results imply that the addition of environmental knowledge and pro-environmental self-identity to the theory of planned behavior is applicable in predicting pro-environmental behavior; specifically the purchase of package-free bath products.Practical implications - The results showed how HEIs can encourage its students to purchase package-free bath products. Social implications - The results highlight how social and economic factors play a role in promoting or inhibiting pro-environmental behavior among HEI students.